2019
DOI: 10.1016/j.soilbio.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

14C characteristics of dissolved lignin along a forest soil profile

Abstract: Lignin is a key component of soil dissolved organic carbon (DOC) and is recently suggested to track C-young DOC components. However, direct evidence is still lacking to prove this hypothesis in the soil. Here, utilizing molecular radiocarbon dating, we present the first 14 C dataset on dissolved lignin through a Podzol soil profile. Dissolved lignin and hydroxy phenols had similar 14 C content as soil organic carbon (SOC) and DOC in the surface organic layer. However, in contrast to SOC, both DOC and dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Plant-derived DOM has been previously characterized as more unsaturated and aromatic than microorganism-derived DOM components (Einsiedl et al, 2007;Fellman et al, 2008). The high proportions of polyphenols in H31, H32, and H51 likely identify contributions from the decay of the plant biopolymer lignin (Benk et al, 2018;Jia et al, 2019). In contrast to the contributions of plant-derived DOM to wells H31, H32, and H51, we found high proportions of unsaturated aliphatic and peptide-like DOM components in well H53, indicating microorganism-derived DOM (Kallenbach et al, 2016).…”
Section: Spatial Patterns In Dom Compositionmentioning
confidence: 50%
“…Plant-derived DOM has been previously characterized as more unsaturated and aromatic than microorganism-derived DOM components (Einsiedl et al, 2007;Fellman et al, 2008). The high proportions of polyphenols in H31, H32, and H51 likely identify contributions from the decay of the plant biopolymer lignin (Benk et al, 2018;Jia et al, 2019). In contrast to the contributions of plant-derived DOM to wells H31, H32, and H51, we found high proportions of unsaturated aliphatic and peptide-like DOM components in well H53, indicating microorganism-derived DOM (Kallenbach et al, 2016).…”
Section: Spatial Patterns In Dom Compositionmentioning
confidence: 50%
“…Regarding our calculated contribution from GOC to OC in the sediments, the assumed range of biogenic 14 C ages from 1,000-4,000 yrs. BP is within the typical range for ages of dissolved OC leaching from soils (Artinger et al, 1996, Jia et al, 2019. Despite this, the range from 1,000-4,000 yrs.…”
Section: Geogenic Organic Carbon In the Sedimentsmentioning
confidence: 58%
“…The OCL OC value displayed a contrary tendency to the N/C ratio (Figure B) for the soil at different depths, indicating that SOM in the topsoil (above 40 cm) accumulated more aromatic carbon than the subsoil. In general, plant-derived OM is dominated by lignins and tannin-like substances, which are more resistant to degradation due to their stable aromatic structure, especially in the early stages of decomposition, , or the inhibitory effects of these compounds on enzyme activity, while microbial-derived OM mainly contains polysaccharides, lipids, and protein-like substances, which are composed of a majority of aliphatic carbons. Previous studies have reported that plant-derived polyphenol compounds and tannins can be selectively adsorbed to reactive iron/aluminum minerals and become less abundant in deeper soils. , This may lead to a low accumulation of aromatic carbons in the underlying soil, and the OCL OC values successfully reflected such change of SOM in the forest soil profile. In addition, we can roughly estimate the aromatic C% in SOM according to the obtained linear equation (aromatic C% = 6.03 × OCL OC + 9.71, R 2 = 0.89, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%